Analysis of influencing factors and establishment of prediction model for successful vaginal delivery after cesarean section - Zhang, Hongxia; Yu, Lin; Wei, Songquan; Li, Guiming (Frontiers in Global Women's Health, 2025)
ObjectiveTo explore the influencing factors of vaginal delivery after cesarean section, establish a predictive model, and identify potential factors for perinatal complications.Materials and methodsThis is a retrospective analysis of women who attempted a trial of labor after cesarean section(TOLAC) at the Third Affiliated Hospital of Guangzhou Medical University and subsequently gave birth in this hospital between 31 December 31 2017 and December 2023. Associations between maternal characteristics and success of TOLAC were assessed using univariate and logistic regression. A predictive model was developed and performance was assessed using the acceptor-operator curve (ROC).ResultsA total of 10,277 pregnant women with a history of previous cesarean section were identified during the observation period, 1,065 attempted TOLAC, which 839 were successful vaginal birth after cesarean (VBAC) and 226 failed vaginal trials. We have developed and validated a simple nomogram prediction model based on common antenatal predictors, which are independently associated with successful TOLAC, including maternal age, height, cervical Bishop score, estimated fetal weight, and use of oxytocin and artificial rupture of membranes to induce labor. The prediction model has been established and verified, and the model demonstrates good prediction efficiency, with an area under the ROC curve of 83.1%. Compared with the TOLAC-failure group and the ERCD group, the VBAC group had the lowest amount of bleeding in intrapartum and 24 h after delivery, puerperal infection, and uterine rupture. Nevertheless, the prevalence of placental abruption and the incidence of neonatal neonatal intensive care unit were higher in this cohort.ConclusionTOLAC is an important public health strategy in China. The results of our study can be used to improve counselling, reduce decision-making conflicts and increase the success rate of trials of vaginal delivery, ultimately improving the prognosis for mother and baby, by providing case-specific possibilities for counselling and management of women with a history of caesarean section and according to the characteristics of each pregnancy.